Chemical modification produces species-specific changes in Cucurbitacin Antifeedant effect - Lang, Karen L. (2013)
Cucurbitacins are secondary metabolites that mediate insect plant interactions not only as allomones against generalists but also as kairomones for specialist herbivores. This study was undertaken to identify the potential of cucurbitacin derivatives as insect antifeedant agents. The antifeedant capacity against a Cucurbitaceae specialist [Epilachna paenulata (Coleoptera: Coccinellidae)] and a polyphagous insect [Pseudaletia adultera (Lepidoptera: Noctuidae)] was evaluated in preference tests in which the insects were given a choice between food plants either treated with the cucurbitacin derivatives or treated with the solvent. The activity was found not to be related to the basic cucurbitacin skeleton, as only 15 of the 28 tested cucurbitacin derivatives were active. Only one of the tested compounds was phagostimulant to the specialist insect (the hemissuccinate of 16-oxo-dihydrocucurbitacin B derivative), while all other active derivatives were deterrent against one of the insects (13 compounds) or both of them (3 compounds). Changes in ring A of the cucurbitacins, as well as in the side chain, modified the activity. As a general trend, when chemical modifications of the basic structure produced a change in activity, the response was opposite in both insects used as biodetectors, indicating that a selective variation in the activity may be achieved by chemical modifications of the cucurbitacin skeleton.